Inverted Linear Correlation Between the Catalytic Activity of Iron Phthalocyanines and the Formal Potential of the Catalyst in the Electrooxidation of L-Cysteine - Zagal-Moya, J; Zagal-Moya, J; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Rojas, J; Silva-Rojas, J (2012)
The formal potential of macrocyclic complexes is a reactivity index that can serve to predict their electrocatalytic activity. We have investigated the effect of the Fe(II)/(I) formal potential E°? of several iron phthalocyanines preadsorbed on graphite electrodes on their catalytic activity for the electrooxidation of l-cysteine. A linear and inverted correlation is observed between the catalytic activity (as log I at constant E) versus the Fe(II)/(I) formal potential of the catalyst, i. e., the activity decreases as the driving force of the catalyst increases. The slope of the correlation is close to -2RT/F and seems to be the falling region of an incomplete volcano plot so the decrease of the activity with increasing E°? can be attributed to a gradual increase in the coverage of l-cysteine molecules adsorbed on the Fe sites with a subsequent decrease in free Fe(II) active sites. © 2012 Springer Science+Business Media, LLC.